Microbiology an introduction - Tortora, Gerard J.; Funke, Berdell R.; Case, Christine L. 1948- (Pearson, 2016)
The twelfth edition focuses on big picture concepts and themes in microbiology, encouraging students to visualize and synthesize more difficult topics such as microbial metabolism, immunology, and microbial genetics